Development of seismic fragility curves for mid-rise masonry infilled reinforced concrete building by incremental dynamic analysis - Patil, V.S.; Tande, S.N. (Journal of Structural Engineering, 2024)
The present work is to study the effect of Brick Masonry Infill (BMI) in reinforced concrete (RC) building on seismic fragility curves using Incremental Dynamic Analysis (IDA). Multiple IDA curves which capture the ground motion uncertainties and which govern the shape of fragility curves are developed for twenty real ground motions. Spectral acceleration-based fragility curves and damage probability matrix under various damage states are developed for midrise RC frames with and without BMI. The comparative fragility curves for buildings with and without BMI are presented. It is concluded that the BMI frame have shown superior performance during earthquake in all modes of different damage states and the dispersion of Damage Measures (DM) and Intensity Measures (IM) in IDA analysis are less in the case of BMI thus improve robustness of the building response results in predictability in design.